ANALISIS KEPEMIMPINAN KEPALA SEKOLAH DALAM MENUMBUHKAN KEMAMPUAN LITERASI SISWA DI SDN 3 TRUWOLU KABUPATEN GROBOGAN - Rinawati, Rinawati; Darmuki, Agus; W, Sri Surachmi (Universitas Muria Kudus, 2024)
This research aims to analyze the relationship between the principal's leadership and students' literacy skills at SDN 3 Truwolu, Ngaringan District, Grobogan Regency. This research uses a qualitative descriptive method, with the school principal as the research subject. Data collection was carried out through observation, interviews and documentation studies. The results of the research show that there is a positive or significant relationship between the principal's transformational leadership and increasing students' literacy skills, as shown by the results of educational report cards which have increased significantly from the previous year. The principal's effective leadership in motivating and empowering teachers, creating comprehensive literacy policies, providing adequate resources, and creating a conducive school environment has had a significant impact on the growth of students' literacy skills at SDN 3 Truwolu.